Israeli society, the Holocaust and its survivors - Porat, Dinah 1943- (Vallentine Mitchell, 2008)
David Ben-Gurion and the Holocaust -- The Allies, Herzl's Testament, the Holocaust, and limitations of Jewish policies, July 1944 -- Martin Buber in Eretz-Israel during the Holocaust years, 1942-1944 -- "Al-Domi" : Palestinian intellectuals and the Holocaust, 1943-1945 -- With forgiveness and grace : the encounter between Ruzka Korczak, the Yishuv, and its leaders, 1944-1946 -- The Transnistria Affair and the rescue policy of the Zionist leadership in Palestine, 1942-1943 -- Hungary, 19 March-19 July 1944 : did the Yishuv know? -- One side of a Jewish triangle in Italy : the encounter of Italian Jews with Holocaust survivors and with Hebrew soldiers and Zionist representatives in Italy, 1944-1946 -- "A year of extermination" : a document on the attitude of the Yishuv in Eretz-Israel toward youth movements in Europe during the Holocaust -- Zionist pioneering youth movements in Poland and their attitude to Eretz-Israel during the Holocaust -- The impact of the war on the Zionist pioneering youth movements in Poland during the Shoah -- Palestinian Jewry and the Jewish Agency : public response to the Holocaust -- The story of 29,000 immigration certificates for children -- Diaspora negation and rescue during the Holocaust : a contradiction? -- The role of European Jewry in the plans of the Zionist movement during the Second World War and its aftermath -- Attitudes of the young state of Israel toward the Holocaust and its survivors : a debate over identity and values -- Teaching the Holocaust to Israeli students, 1974-1987 -- "Amalek's accomplices" : blaming Zionism for the Holocaust : anti-Zionist ultra-orthodox circles in Israel during the 1980s -- Attitudes within Israeli society toward the Jews of Europe and Holocaust survivors in the 1990s -- Some effects of the Holocaust on Israeli demography and foreign policy